KAJIAN PENERAPAN CARA PRODUKSI YANG BAIK DAN PROSEDUR OPERASI SANITASI DALAM PENYELENGGARAAN WARUNG TEGAL - Bambang Suparmono; Elis Dihansih; Mohamad Ali Fulazzaky (Jurnal Ilmiah Pangan Halal, 2020)
This study aims to determine the ability and real picture of warteg in the application of food safety, aspects of GMP (Good Manufacturing Practices) which are inhibiting factors for the application of food safety, implementation of SSOP (Standard Sanitation Operating Procedures). The research design is an assessment of the application of GMP by using a processing facility inspection form (BPOM, 1999) or by using a revised draft of the CPMB examination form (BPOM, 2005). After the data is collected, problem identification is carried out by referring to the results of the assessment of the application of GMP in processing facilities. SSOP and list of forms are prepared based on the identification results. Research on the questionnaire checklist to 65 respondents about GMP and SSOP statistically, namely; The numbers obtained (r Pearson) are compared with the r table for α = 0.05 with N = 65 at 0.2027. Based on the analysis results it can be seen that items 11, 15, 23, and 24 have a correlation value less than 0.2027. The results of the assessment of the weight of the GMP application at the warteg are in accordance with KEPMENKES RI 715 / MENKES / SK / V / 2003 with a total score of 62 that has not met the minimum score of 70 from the maximum value of 82, this is caused by several factors such as location, air conditioning system, employee hygiene , employee discipline, use of equipment and materials, repeated cooking processes, use of Food Additive, very low wages, the training program from the related agency is still not sustainable.